Development of Entrepreneurship Scale Towards University Students - Nurluöz, Özdem (2019)
The aim of this study is to develop a reliable and valid measurement tool to evaluate the entrepreneurship characteristics of university students. The study group is comprised of 386 students at the Faculty of Nursing, Near East University. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were applied in order to assess the construct validity of entrepreneurship scale. Prior to the application of Exploratory Factor analysis, Kolmogrov Smirnov, Shapiro Wilks tests were applied in order to identify whether the data set shows normal distribution; QQ plot was analysed with regard to the distribution and the skewness and kurtosis values of distribution were checked accordingly. In consideration with the generated results, the data set was considered as showing normal distribution. Upon ensuring the normality assumption required for the Exploratory Factor analysis, Kaiser-Mayer-Olkin (KMO) coefficient and Barlett sphericity test that are used in the identification of data eligibility for the Exploratory Factor Analysis were applied respectively. The findings with regard to the reliability of scale were ensured with Cronbach Alpha (internal consistency). The findings showed that the reliability coefficient for internal consistency is sufficient. It is concluded that our study can be used in scientific researches since it was checked in terms of validity and reliability.